Management Training in the Republic of Dagestan in the Face of Modern Challenges (On the 5th Anniversary of the Faculty of Management of Dagestan State University) - G. U. Magomedbekov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2019)
The article is devoted to the issues of managerial training in the Republic of Dagestan. The role of the Faculty of Management of the Dagestan State University in their preparation is determined.